Choroidal thinning in myopia is associated with axial elongation and severity of myopic maculopathy - Momoka Midorikawa; Kiwako Mori; Hidemasa Torii; Yohei Tomita; Yan Zhang; Kazuo Tsubota; Toshihide Kurihara; Kazuno Negishi (Scientific Reports, 2024)
Abstract High myopia can lead to pathologic myopia and visual impairment, whereas its causes are unclear. We retrospectively researched high myopia cases from patient records to investigate the association between axial elongation and myopic maculopathy. Sixty-four eyes were examined in patients who visited the department between July 2017 and June 2018, had an axial length of 26 mm or more, underwent fundus photography, and had their axial length measured twice or more. The average axial length was 28.29 ± 1.69 mm (mean ± standard deviation). The average age was 58.3 ± 14.4 years old. Myopic maculopathy was categorized as mild (grades 0 and 1) and severe (grades 2, 3, and 4). The severe group had longer axial lengths than the mild group (P < 0.05). Moreover, the severe group exhibited thinner choroidal thickness than the mild group (P < 0.05). When subjects were grouped by axial elongation over median value within a year, the elongation group showed thinner central choroidal thickness than the non-elongation group (142.1 ± 91.9 vs. 82.9 ± 69.8, P < 0.05). In conclusion, in patients with high myopia, the severity of maculopathy correlated with choroidal thickness and axial length. Thinner choroidal thickness was associated with axial elongation based on the baseline axial length.